EFFECTS OF A COMBINED EXERCISE ON CAROTID ARTERY PARAMETERS IN ELDERLY WOMEN WITH SARCOPENIC OBESITY - Park, J. (Innov Aging, 2017)
Sarcopenic obesity is more closely associated with cardiovascular disease (CVD) than non sarcopenic obesity the older population. Higher body fat mass and age-related loss of the skeletal muscle mass is closely associated with increases of carotid artery intima-media thickness (CIMT). The aim of this study was to examine the effectiveness of a 24 week combined exercise program on carotid parameters in elderly women with sarcopenic obesity. Fifty sarcopenic obesity elderly women (74.1 ± 6.1 years) were randomly allocated into either the exercise or control groups. The exercise group performed supervised strength and aerobic combined exercise over 24 weeks, for a 50–80 minutes, 5 times a week. CIMT, systolic flow velocity (PSV), carotid luminal diameter (CLD), diastolic flow velocity (EDV), and wall shear rate (WSR) were measured using B mode ultrasound. The differences in all carotid variables and the relative changes between baseline and 24 weeks, follow up were evaluated. In the analysis of variance results, CIMT (p = 0.013), PSV (p = 0.007), EDV (p =0.006), and WSR (p = 0.010) showed significant group × time interactions. Despite the CLD did not change, CIMT significantly decreased (p < 0.01), PSV (p < 0.01), EDV (p <0.001), and WSR (p < 0.05) were significantly increased after 24 weeks in exercise group. The results suggest this combined exercise intervention could be an effective approach to reduce CAD risk by ameliorating the risk factors for CAD in elderly community-dwelling women with sarcopenic obesity.